Mobile Genetic Elements in Cellular Differentiation, Genome Stability, and Cancer - Jose Luis Garcia Perez (Frontiers Research Topics, 2018)
The human genome, as with the genome of most organisms, is comprised of various types of mobile genetic element derived repeats. Mobile genetic elements that mobilize by an RNA intermediate, include both autonomous and non-autonomous retrotransposons, and mobilize by a "copy and paste" mechanism that relies of the presence of a functional reverse transcriptase activity. The extent to which these different types of elements are actively mobilizing varies among organisms, as revealed with the advent of Next Generation DNA sequencing (NGS).To understand the normal and aberrant mechanisms that impact the mobility of these elements requires a more extensive understanding of how these elements interact with molecular pathways of the cell, including DNA repair, recombination and chromatin. In addition, epigenetic based-mechanisms can also influence the mobility of these elements, likely by transcriptional activation or repression in certain cell types. Studies regarding how mobile genetic elements interface and evolve with these pathways will rely on genomic studies from various model organisms. In addition, the mechanistic details of how these elements are regulated will continue to be elucidated with the use of genetic, biochemical, molecular, cellular, and bioinformatic approaches. Remarkably, the current understanding regarding the biology of these elements in the human genome, suggests these elements may impact developmental biology, including cellular differentiation, neuronal development, and immune function. Thus, aberrant changes in these molecular pathways may also impact disease, including neuronal degeneration, autoimmunity, and cancer.